2013
DOI: 10.12669/pjms.294.3626
|View full text |Cite
|
Sign up to set email alerts
|

Perception on the severity of unwanted pregnancyamong university students

Abstract: Objectives: The purpose of this study was to examine the perception of University students regarding the severity of unwanted pregnancy. Methods: This cross sectional study involved 408 (206 females and 202 males) students residing within the university campus. Simple and systematic sampling methods were used to select participants. A 4-likert scaled self-administered questionnaire was used for data collection. Result: Majority (87.70%) of participants perceived unwanted pregnancy as leading to impaired mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Unsurprisingly, Sa-ngiamsak (2016) argues that boyfriends of pregnant students denies and ignores being the father of the unborn baby in order to protect themselves and their futures, hence, pregnant students are reluctant to disclose their pregnancies due to fear of rejection and/or abandonment. Consistent with the present study, Anyanwu et al (2013) showed that pregnant students are embarrassed to reveal their pregnancies to their families, partners and peers. Malhotra (2008), also reported that pregnant females found it difficult to disclose their pregnancies to their social-support system due to fear of abandonment, pain and suffering from the resultant broken relationships with their boyfriends, parents and friends.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unsurprisingly, Sa-ngiamsak (2016) argues that boyfriends of pregnant students denies and ignores being the father of the unborn baby in order to protect themselves and their futures, hence, pregnant students are reluctant to disclose their pregnancies due to fear of rejection and/or abandonment. Consistent with the present study, Anyanwu et al (2013) showed that pregnant students are embarrassed to reveal their pregnancies to their families, partners and peers. Malhotra (2008), also reported that pregnant females found it difficult to disclose their pregnancies to their social-support system due to fear of abandonment, pain and suffering from the resultant broken relationships with their boyfriends, parents and friends.…”
Section: Discussionsupporting
confidence: 92%
“…& Jali, 2014). Student pregnancy is a global trend, although, the problem is more visible in developing countries, such as South Africa (Aluzimbi et al, 2013;Anyanwu et al, 2013;Naidoo & Kasiram, 2006). Pregnant students are victims to a variety of challenges, such as poverty, poor academic performances, and dropping out of their institutions due, mainly, to their inability to concentrate on their studies (Changach, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The reported middle age of most of the participants is understandable, as the majority of them were students. Most undergraduate students in Nigerian universities are about this age group, as shown in studies from different regions of the country [15][16][17][18][19][20][21][22][23]. The marital status of the participants in the study was not obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding the sampling procedure, instrumentation and data collection procedures are reported elsewhere. 17 Permission to conduct the research was given by the University of Venda, health, safety and research ethics committee: SHS/12/PH/06/0912.…”
Section: Methodsmentioning
confidence: 99%